The Effect of Problem-Based Learning Using Simulators on CPS Skills and Learning Outcomes of Lighting Systems - Handoyono, Nurcholish Arifin; Alvianto, Ahmad (Journal of Vocational Education Studies, 2024)
Collaborative Problem Solving (CPS) skills  are a skill that must be possessed in the 21st century, besides that learning outcomes must also be better in order to become Vocational High School graduates who are ready to become a professional workforce. One of the learning methods that can be applied is Problem-Based Learning (PBL) using simulators. The purpose of this study was to determine the PBL method using simulators to have a better influence than the lecture method on CPS skills and learning outcomes of student lighting systems. The type of research used is a quasi-experiment with non-equivalent group design. The population in this study was class XI TKR Vocational High School Muhammadiyah 1 Bambanglipuro, the sample selection in this study used Cluser Random Sampling, from 4 classes selected XI TKR A Experiment, XI TKR B Control. The instruments of this study are the width of the CPS skill questionnaire and pretest & posttest student learning outcomes. Data analysis technique using t-test preceded by prerequisite tests, namely normality test and homogeneity test. The research results show that the CPS skills and learning outcomes of lighting system students are better using the PBL method than the lecture method. The implication of this research is that teachers can use this method as an alternative learning strategy to improve students' CPS skills as creative problem solvers.